Confounding the process: forgotten actors and factors in the state-corporate crime paradigm - Griffin, O. Hayden (Crime, law and social change, 2016)
The state-corporate crime paradigm, which has evolved from the foundational work of Edwin Sutherland and subsequent generations of corporate crime research, has contributed to a more satisfying structural account of the manner in which combinations of corporate malfeasance and government/regulatory policy can result in social harm. While this paradigm certainly enhances the understanding of the production of social harm at the nexus of state-corporate action, we argue that the analysis of specific case studies can and should be further enriched with attention to two particular points of focus. In the first instance, we argue, case studies should consider the utility of organizational frames and their variation in explaining both state and corporate behavior. In addition, state-corporate crime research is considerably aided by detailed examination of the social and cultural contexts of the risk calculations that inform critical decision-making.